The Role of Serotonin in the Influence of Intense Locomotion on the Behavior Under Uncertainty in the Mollusk Lymnaea stagnalis - Aonuma, Hitoshi; Mezheritskiy, Maxim; Boldyshev, Boris; Totani, Yuki; Vorontsov, Dmitry; Zakharov, Igor; Ito, Etsuro; Dyakonova, Varvara (Frontiers in Physiology, 2020)
The role of serotonin in the immediate and delayed influence of physical exercise on brain functions has been intensively studied in mammals. Recently, immediate effects of intense locomotion on the decision-making under uncertainty were reported in the Great Pond snail, Lymnaea stagnalis (Korshunova et al., 2016). In this animal, serotonergic neurons control locomotion, and serotonin modulates many processes underlying behavior, including cognitive ones (memory and learning). Whether serotonin mediates the behavioral effects of intense locomotion in mollusks, as it does in vertebrates, remains unknown. Here, the delayed facilitating effects of intense locomotion on the decision-making in the novel environment are described in Lymnaea. Past exercise was found to alter the metabolism of serotonin, namely the content of serotonin precursor and its catabolites in the cerebral and pedal ganglia, as measured by high-performance liquid chromatography. The immediate and delayed effects of exercise on serotonin metabolism were different. Moreover, serotonin metabolism was regulated differently in different ganglia. Pharmacological manipulations of the serotonin content and receptor availability suggests that serotonin is likely to be responsible for the locomotor acceleration in the test of decision-making under uncertainty performed after exercise. However, the exercise-induced facilitation of decision-making (manifested in a reduced number of turns during the orienting behavior) cannot be attributed to the effects of serotonin.